Hubungan Asupan Karbohidrat dan Serat Dengan Kejadian Diabetes Melitus Tipe II di Wilayah Kerja Puskesmas Purwosari - Amanina, Azka, Bejo Raharjo, SKM, M.Kes, Farid Setyo Nugroho, SKM (2015)
Diabetes mellitus is one kind of degenerative diseases that its prevalence is increase year by year in Indonesia even in the world. According to International Diabetes Federation (IDF) data, on 2013 more than 328 million people in the world suffering from diabetes mellitus type II. The objective of this research was to analyze the relation between carbohydrate and fiber intake and the incident of diabetes mellitus type II in working area of Purwosari health centers. The kind of the research was observational research with case control project. The case population is people suffering from DM type II on March-May 2015, there are 60 people, while the control population is people without DM type II. The selection sample for case group there are 40 people and the control group are 40 people which is done by using Simple Random Sampling, whereas the statistic test is using Chi Square test. The results showed that the intake of carbohydrates in Puskesmas Purwosari average carbohydrate intake for the group amounted to 69.07 cases, exceed the RDA is 45-65% per day, for the control group the average intake of carbohydrates is 64.70, which is in line with the recommendation AKG. While the average fiber intake for both groups of cases (19.35) and the controls (21.01) has a fiber intake is not in accordance with the recommendation AKG day ranged between 25-35 grams. The results of this study indicate that there is a relationship between results of this research show that there is relation between carbohydrate intake and the incident of diabetes mellitus type II in working area of Purwosari health centers (p = 0,004; OR = 3,857; 95% CI = 1,526-9,750), there is relation between fiber intake and the incident of diabetes mellitus type II in working area of Purwosari health centers (p = 0,043; OR = 2,538; 95% CI = 1,023-6,298). Key Words : Carbohydrate Intake, Fiber Intake, Diabetes Mellitus type II